THE EFFECT OF THE JIGSAW-TYPE COOPERATIVE MODEL WITH THE ASSISTANCE OF PAIRED CARD MEDIA ON THE LEARNING OUTCOMES OF GRADE VII STUDENTS AT KRISTEN PAYETI JUNIOR HIGH SCHOOL - Yorti Yowa Tangu; Vidriana Oktoviana Bano; Yohana Ndjoeroemana (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of the jigsaw-type cooperative model assisted by paired card media on the learning outcomes of class VII students on the interaction of living things with the environment at Payeti Christian Middle School. This type of research is an experiment using a pretest-posttest control group design, sampling using purposive sampling. The population in this study were all students of class VII IPA at Payeti Christian Middle School in the even semester of the 2022/2023 academic year. The sample of this research was 30 students of class VII C as the control class and 30 students of class VII B as the experimental class. The results of the descriptive analysis obtained showed that the pretest and posttest scores for the experimental class were 59.50 < 77.00 while the pretest and posttest scores for the control class were 45.50 < 72.97. Further testing the hypothesis using the paired sample t-test produces an Asymp value. Sig (2-tailed) 0.000 means that the value is less than 0.05 (< 0.05). It can be concluded that the jigsaw-type cooperative learning model assisted by paired card media affects learning outcomes.Keywords: Learning Model, Cooperative, Jigsaw, Paired Cards, Learning OutcomesAbstrakPenelitian ini bertujuan untuk mengetahui pengaruh model kooperatif tipe jigsaw berbantuan media kartu berpasangan terhadap hasil belajar siswa kelas VII materi interaksi makhluk hidup dengan lingkungan di SMP Kristen Payeti. Jenis penelitian ini ialah eksperimen menggunakan desain pretest-posttest control group design, Pengambilan sampel menggunakan purposive sampling. Populasi dalam penelitian ini seluruh siswa kelas VII IPA di SMP Kristen Payeti pada semester genap tahun ajaran 2022/2023. Sampel penelitian ini yaitu 30 siswa kelas VII C sebagai kelas kontrol dan 30 siswa kelas VII B sebagai kelas eksperimen. Hasil analisis deskriptif yang diperoleh menunjukkan bahwa nilai pretest dan posttest kelas eksperimen 59.50 < 77.00 sedangkan nilai pretest dan posttest kelas kontrol 45.50 < 72.97. Lebih lanjut pengujian hipotesis menggunakan uji paired sample t test menghasilkan nilai Asymp. Sig (2-tailed) 0,000 artinya nilai tersebut kurang dari 0,05 (< 0,05). Dapat disimpulkan bahwa model pembelajaran kooperatif tipe jigsaw berbantuan media kartu berpasangan berpengaruh terhadap hasil belajar.Kata Kunci: Model Pembelajaran, Kooperatif, Jigsaw, Kartu Berpasangan, Hasil Belajar